IMPLEMENTATION OF MONOCULTURAL PLANT PATTERNS IN DESA OENENU INDUK, KABUPATEN TIMOR TENGAH UTARA, PROVINSI NUSA TENGGARA TIMUR, KELOMPOK TANI “MEKAR SARI” - Asep Ikhsan Gumelar; Isman Sidik (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Oenenu Induk village has the potential for monoculture farming that needs to be developed because it has fertile land and has natural resources such as water and a climate that allows kale to thrive. The advantages of monoculture farming systems are that they can increase agricultural yields and also have greater growth and yields than competition between other crops. The purpose of this activity is to introduce monoculture cropping patterns by optimizing narrow land with satisfactory results, to improve the literacy of farmer groups with these crops and to determine the efficiency of use. The method used is training and mentoring. Monoculture cropping patterns can simplify the process of cultivating kale and increase production.